Practices of the Plantation in La loma del ángel - Lanie Millar (Studies in 20th & 21st Century Literature, 2013)
Most analyses of Cuban author Reinaldo Arenas’s 1987 La loma del ángel, a parodical rewriting of Cirilo Villaverde’s 1882 classic Cecilia Valdés, focus on the author’s criticism of racial discrimination inherited from Cuba’s slaving society, on an allegorical condemnation of Castro’s post-revolutionary Cuba, or on the author’s creative, carnivalesque use of language. This article argues that an alternative understanding of La loma del ángel demonstrates Arenas’s circular and fatalistic historical vision, in which the exploitive plantation system reappears in different forms through Cuban history. It places La loma del ángel into the context of Arenas’s other writing about the plantation in his poetic work El central and his autobiography Antes que anochezca, which together suggest that the continuities of the violence of the plantation system form the historical trajectory of Cuba’s history since Spanish colonization. Using theoretical work on the Plantation in the Caribbean by Antonio Benítez Rojo, Manuel Moreno Fraginals, Gustavo Pérez Firmat and Édouard Glissant, this article shows that in La loma del ángel, arts such as dance, music and literature represent a powerful yet fleeting antidote to the abuses of this system.
Keywords: Reinaldo Arena; La loma del ángel; Cirilo Villaverde; Cecilia Valdés; literary criticism; Cuba; Cuban history; plantation